Effects of neurostimulation and motivating patriotic music on reserve officer training unit cadets running performance and mood states - Jaapar, Siti Hawa Zulaikha (2018)
Transcranial neurostimulation can improve bodily function through training the brain and the central nervous system. Besides that, there are also increasing evidence that the “right” music can increase performance. This study examined the effects of neurostimulation and motivating patriotic music on running performance and mood states of 22 male ROTU cadets. All the participants participated in all three research conditions which were no stimulation, neurostimulation and motivating patriotic music, but at different times with one week of rest in between conditions. Upon receiving the stimulation, the participants did Multistage Fitness Test (MSFT) to measure their running performance. Mood states of the participants were taken before stimulation, after stimulation and after performing MSFT by using Brunel Mood Scale (BRUMS) questionnaire. There were no statistically significant differences in the running performance between no stimulation, neurostimulation and motivating patriotic music. For stimulation by using motivating patriotic music, we found out that there were statistically significant differences in fatigue, tension and vigour mood states across the three times. As for neurostimulation, we found out that there were statistically significant differences in all six BRUMS items that we assessed. We conclude that neurostimulation and motivating patriotic music did not increase the running performance of ROTU cadets. Both neurostimulation and listening to motivating patriotic music can enhance mood states before a running performance test. Motivating patriotic music was shown to give greater mood responses when compared to neurostimulation.